Relation of left bundle branch block in type 2 diabetes mellitus with left ventricular systolic functions and hemoglobin A1c - Saravi, Mehrdad (Array, 2007)
The aim of the study was evaluation of left bundle branch block (LBBB) as a marker of cardiovascular involvement in diabetes mellitus (DM) patients by examining left ventricular systolic function and hemoglobin A1c. Data on 25 DM patients with LBBB were compared with data on 25 DM patients without LBBB and 25 non-DM patients with LBBB. The mean age of patients in DM with LBBB, DM without LBBB, and non-DM with LBBB groups was 62.2±9.4, 62±6.3 and 63.6±8 years, respectively (p=NS).